Knowledge, Attitude and Practice of Mothers about Perinatal Care - Shalini Hajela (International Journal of Medical Research and Review, 2014)
Background: Infant Mortality Rate (IMR), the most sensitive indicator of health is reflected by female literacy, health education and nutrition of mother and infant. The present study is aimed to assess the Knowledge, Attitude and Practice of mothers regarding perinatal care, nutrition in pregnancy, place and method of delivery, breast feeding, prelacteal feeds, care of newborn, vaccination and red flag signs in newborn.Methods: The study was conducted to determine the Knowledge, Attitude, Practices amongst mothers (250 families), regarding perinatal care and to study the effect of health education. A pretested questionnaire was adopted after a short pilot study. Proportions were calculated for all observations and Z-test was applied for comparison between observations.Results: The majority of the respondents had correct knowledge regarding antenatal care, hospital delivery (88%), selection of clean place for delivery, delivery to be conducted by doctors, nurses or trained birth attendants (97.2%), cord cutting (83.6%), cord care(52.4%), rooming in (88%), hypothermia prevention (72.4%) and physiological jaundice of newborn (81.2%). Most had incorrect knowledge regarding type of diet and time of initiation of nutritious diet after delivery, infant feeding in relation to initiation of first feed (58%), colostrum being beneficial and giving prelacteal feeds (52.4%), kajal application (68.4%) and oil instillation in ears (72%).Conclusions: Successful maternal and child health depends largely on perinatal care viz. pregnancy, antenatal care, nutrition, spacing between pregnancies, basic hygiene, domiciliary delivery, care of the newborn and prevention from infection. Thus, health education regarding perinatal care is important for both mother and child.